Penerapan Metode Mind Mapping pada Model Direct Instruction untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Siswa SMPN 16 Mataram - Rika Venisari; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The purpose of research is to improving problem solving skill of physics at student in SMPN 16 Mataram used mind mapping method at direct instruction model. Subyek research is VIII-E class with 32 students. The type of research is Classroom Action Research which done 2 cycle which consist of planning phase, execution, observation, evaluation, and reflection. Student and teacher activity data were get from observation sheet, and students learning result were get from test in the end of each cycle. Efficacy indicator of this research is if the category activity student is active and be improve, learning result of students is complete clasicality, which students get score Ã¢â°Â¥ KKM value 75 have reached Ã¢â°Â¥ 85 % from student grand total following evaluation. The result of this research showing the student activity and learning result is improved. In first cycle got mean score activity student is 10,5 with category active enough, and class mean is 73.6 with clasical complete 65.6 %. In second cycle got mean score activity student is 13,5 with category active, and mean class is 80.9 with complete classical is 87.5%. Based on the results got from each cycle, it can be concluded that the implementation of mind mapping method on direct instruction model can increase the physics problem solving skill of student of SMPN 16 Mataram, specially in vibration and wave chapter.